Evaluating the effects of air disinfectants in decontamination of COVID‐19 aerosols. Issue 1 (10th January 2023) - Dehghani, Soheil; SeyedAlinaghi, SeyedAhmad; Karimi, Amirali; Afroughi, Fatemeh; Abshenas, Shayan; Azad, Kimia; Tantuoyir, Marcarious M.; Mohammadi, Parsa; Ghavam, Seyed Mohammad; Mojdeganlou, Hengameh; Dadras, Omid; Nazarian, Newsha; et al.
Abstract: Introduction: Airborne transmission is the most crucial mode of COVID‐19 transmission. Therefore, disinfecting the severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) aerosols float can have important implications in limiting COVID‐19 transmission. Herein, we aimed to review the studies that utilized various disinfectants to decontaminate and inactivate the SARS‐CoV‐2 aerosols. Methods: This study was a review that studied related articles published between December 1, 2019 and August 23, 2022. We searched the online databases of PubMed, Scopus, Web of Science, Cochrane, on August 23, 2021. The studies were downloaded into the EndNote software, duplicates were removed, and then the studies were screened based on the inclusion/exclusion criteria. The screening process involved two steps; first, the studies were screened based on their title and abstract and then their full texts. The included studies were used for the qualitative analysis. Results: From 664 retrieved records, only 31 met the inclusion criteria and were included in the final qualitative analysis. Various materials like Ozone, H2 O2, alcohol, and TiO2 and methods like heating and using Ultraviolet were described in these studies to disinfect places contaminated by COVID‐19. It appeared that the efficacy of these disinfectants varies considerably depending on the situation, time, and ultimately their mode of application. Conclusion: Following reliable protocols in combination with the proper selection of disinfectant agents for each purpose would serve to achieve desired elimination of the SARS‐CoV‐2 transmission.